Artificial Intelligence in Medical Science: Navigating Promise and Peril – an editorial (The Insight, 2025)
The accelerating integration of artificial intelligence (AI) into medical science marks a pivotal moment for global health systems. Once considered a speculative tool, AI is rapidly becoming an essential component of diagnostics, therapeutics, and health-care delivery. Yet its future role will be defined not by technological capability alone, but by our collective willingness to govern it responsibly, equitably, and transparently.In diagnosis, AI has demonstrated clear value. Deep-learning models can detect abnormalities in radiology and digital pathology with a consistency that often narrows inter-observer variation. Early evidence from prospective studies suggests that AI-assisted reporting can reduce time to diagnosis and support overburdened clinical services without compromising safety.